Investigating the nervous system (Chatsworth, CA : AIMS Multimedia, 1997)
This cd-rom contains complete linear video, interactive quiz with video reinforcement, bulletin board, glossary, test with record keeping and teacher management system.
This cd-rom is available at Makmal Digital, PPKL
Keywords: Nervous System -- anatomy & physiology